Unique immune characteristics and differential anti-PD-1-mediated reinvigoration potential of CD8+ TILs based on BRCA1/2 mutation status in epithelial ovarian cancers - SungHoon Kim; Sang Wun Kim; Su-Hyung Park; Eui-Cheol Shin; Junsik Park; Yong Jae Lee; Jung Yun Lee; Mi-Kyoung Seo; Jung Chul Kim (Journal for ImmunoTherapy of Cancer)
Background We aimed to investigate the distinct immunological characteristics of the tumor immune microenvironment in epithelial ovarian cancer (EOC) according to BRCA1/2 mutations status and differential PD-1 expression levels.Methods Tumor-infiltrating lymphocytes (TILs) were collected from patients with newly diagnosed advanced-stage EOC (YUHS cohort, n=117). This YUHS cohort was compared with The Cancer Genome Atlas (TCGA) data for ovarian serous cystadenocarcinoma (n=482), in terms of survival outcomes and immune-related gene profiles according to BRCA1/2 status. We used multicolor flow cytometry to characterize the immune phenotypes and heterogeneity of TILs with or without BRCA1/2 mutations. In vitro functional assays were conducted to evaluate the reinvigorating ability of CD8+ TILs on anti-PD-1 treatment.Results We found that EOC patients with BRCA1/2 mutations (BRCA1/2mt) exhibited better survival outcomes and significantly higher tumor mutation burden (TMB), compared with BRCA1/2 non-mutated (BRCA1/2wt) patients. Furthermore, CD8+ TILs within BRCA1/2mt tumors displayed characteristics indicating more severe T-cell exhaustion than their BRCA1/2wt counterparts. Notably, the capacity for anti-PD-1-mediated reinvigoration of CD8+ TILs was significantly greater in BRCA1/2wt tumors compared with BRCA1/2mt tumors. Additionally, within the BRCA1/2wt group, the frequency of PD-1highCD8+ TILs was positively correlated with the reinvigoration capacity of CD8+ TILs after anti-PD-1 treatment.Conclusion Our results highlight unique immune features of CD8+ TILs in EOC and a differential response to anti-PD-1 treatment, contingent on BRCA1/2 mutation status. These findings suggest that immune checkpoint blockade may be a promising frontline therapeutic option for selected BRCA1/2wt EOC patients.